Modelling air pollution and emergency department visits among children with respiratory diseases in relation to phases of the movement control order (MCO) in Malaysia - Masrani, Afiqah Syamimi (2023)
Introduction: Children’s increased vulnerability towards air pollution exposure, and their increased susceptibility to the adverse effects of air pollution, increases their risk of mortality and morbidity. Their respiratory health is the most affected and has been among the top leading cause for emergency department (ED) visits worldwide. Following the COVID-19 pandemic, an improvement of the world’s air quality was observed secondary to the implementation of state-wide lockdowns, known as the Movement Control Order (MCO), in Malaysia. Therefore, we construct four objectives to model the changes in the relationship between air pollution and ED visits among children with respiratory diseases in relation to the phases of the MCO in two cities in Malaysia which are 1) To determine the changes in the trend of paediatric ED visit; 2) To determine the changes in the trend of paediatric ED visits with respiratory disease; 3) To determine the changes in the trend of air pollution concentrations; and 4) To model and compare the relationship between air pollution and respiratory-related ED visits among children across the pre, during, and post-MCO periods in two Malaysian cities. Methodology: We analysed secondary data of children's ED visits from two public hospitals in Kota Bharu and Johor Bahru cities over five years (17 March 2017 to 17 March 2022). Predictor variables included air pollution index, particulate matter less than 10μm (PM10), particulate matter less than 2.5μm (PM2.5), nitrogen dioxide (NO2), sulphur dioxide (SO2), carbon monoxide (CO), and ozone (O3). Whereas the response variables are the number of children's ED visits and their characteristics which include the triage category, visit outcome, ED diagnosis, and respiratory diagnosis subtype. The study included all children under the age of 18 who fulfils the selection criteria. The study period was divided into three periods based on the MCO in Malaysia, which are the pre-MCO (17 March 2017 to 17 March 2020), MCO (18 March 2020 to 2 January 2022), and post-MCO (3 January 2022 to 17 March 2022) periods. The trend of air pollution concentration and paediatric ED visits’ characteristics were compared between the three periods using Welch t-tests for numerical outcomes and multinomial logistic regressions for categorical outcomes. Changepoint analysis was used to detect any changepoints within the trend of paediatric ED visits whereas generalized additive models were used to examine the relationship between air pollution and children's ED visits for respiratory diseases across the three periods. Result: A total of 175,737 visits were recorded over the five years where nearly 30% (52,704) were diagnosed with a respiratory disease. During the MCO, the children's ED visits decreased by 57.57%. An increase in the proportion of yellow (OR=1.23, 95% CI 1.20 to 1.28, p<0.001) and red (OR=1.79, 95% CI 1.69 to 1.90, p<0.001) triage categories was observed in contrast to a decrease in the proportion of hospitalized cases (OR=0.19, 95% CI 0.18 to 0.19, p<0.001) during the MCO period. Although respiratory diseases remain as the main reason for ED visits across all three periods, we observed changes in the trend of the respiratory subtypes. The odds of being diagnosed with influenza and pneumonia increased significantly during the post-MCO period (Kota Bharu: OR=1.43, 95% CI 1.07 to 1.91, p<0.001; Johor Bahru: OR 1.43, 95% CI 1.15 to 1.78, p<0.001) whilst the odds for chronic lower respiratory disease decreases (Kota Bharu: OR=0.07, 95% CI 0.05 to 0.09, p<0.001; Johor Bahru: OR=0.06, 95% CI 0.05 to 0.07, p<0.001). All air pollutants experienced a significant decline during the MCO and post-MCO periods except for SO2 concentration in the Kota Bharu city for both the MCO (t(1626.18) = 6.78, p<0.001) and post-MCO periods (t(76.63) = 5.05, p<0.001) and CO concentration in Johor Bahru city during the post-MCO period (t(73.18) = 4.84, p<0.001). Our model explained 69.9% (R2 = 0.62) and 53.0% (R2 = 0.49) of the variation in paediatric respiratory ED visits in Kota Bharu and Johor Bahru based on the air pollution concentrations, respectively. In Kota Bharu, PM10 is significantly associated with acute upper respiratory infections during the pre-MCO period (edf = 6.44, p<0.001) but was no longer significantly associated in the post-MCO period. In Johor Bahru, although the number of significant relationships between individual air pollutants to the different respiratory subtypes increased during the MCO period, the significance of these relationships diminishes during the post-MCO period, and the number of significant relationships becomes less compared to the pre-MCO period. Conclusion: The COVID-19 lockdown improved air quality and altered the patterns and causes of paediatric respiratory ED visits in two Malaysian cities. Thus, highlighting air pollution as a significant risk factor for respiratory diseases in children, in Malaysia, with different effects depending on the exposure type and duration. This study suggests some public health recommendations to raise awareness, improve the national pandemic preparedness plan, and introduce early warning systems for air pollution and respiratory diseases in the ED.